2020
DOI: 10.4081/oncol.2020.490
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-PD1 and anti-PD-L1 alike? The non-small-cell lung cancer paradigm

Abstract: Anti-PD1 and anti-PD-L1 agents may have intrinsic and clinically relevant differences in the treatment of non-small cell lung cancer (NSCLC) patients. By reviewing currently available indirect evidence on these agents for NSCLC treatment, highlighting possible inter- and intra-class dissimilarities, anti-PD1 agents showed a higher response rate and a better outcome when combined with chemotherapy for the first-line treatment of patients with squamous and PD-L1 low advanced NSCLC, as compared to anti-PD-L1 agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 60 publications
(128 reference statements)
1
30
0
3
Order By: Relevance
“…Together, these two results might imply that anti‐PD1 antibodies induce stronger antitumoral therapy 20 . These differences might also derive from heterogeneous immunogenicity of the antibodies themselves, eliciting neutralizing antibodies against the anti‐PD1 or ant‐PD‐L1 antibodies that could dampen their activity to different extents 21 …”
Section: Discussionmentioning
confidence: 99%
“…Together, these two results might imply that anti‐PD1 antibodies induce stronger antitumoral therapy 20 . These differences might also derive from heterogeneous immunogenicity of the antibodies themselves, eliciting neutralizing antibodies against the anti‐PD1 or ant‐PD‐L1 antibodies that could dampen their activity to different extents 21 …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which some patients who experience progression after initial immunotherapy may benefit from subsequent immunotherapy is still unclear. One reason for this may rely on differences between PD-1/PD-L1 inhibitors (28). And it may take time for the immune system to activate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the KEYNOTE 045 study, a significant difference in OS was observed in favour of the anti-PD-1 pembrolizumab versus chemotherapy in patients with high PD-L1 tumours defined as CPS according the 22C3 Dako assay [ 57 ]. Although possible differences in efficacy between the anti-PD1 and anti-PD-L1 agents cannot completely be ruled out [ 58 ], plausible explanations may rely on the different tests and scores used to assess the PD-L1 expression, as well as on the tumoural site and timing of the biopsy in respect to the disease history. In this regard, it is noteworthy that the mOS duration in the high PD-L1 subgroup of patients differed between those two trials despite the similar populations enrolled and the mOS observed in the overall population of the chemotherapy control arm (of 8.4 and 7.3 months, for the IMvigor211 and the Keynote-045 study, respectively) [ 56 , 57 ].…”
Section: Molecular Factorsmentioning
confidence: 99%